2013
DOI: 10.1155/2013/815365
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia Presenting as Acute Appendicitis

Abstract: Appendicitis in leukemic patients is uncommon but associated with increased mortality. Additionally, leukemic cell infiltration of the appendix is extremely rare. While appendectomy is the treatment of choice for these patients, diagnosis and management of leukemia have a greater impact on remission and survival. A 59-year-old Caucasian female was admitted to the surgical service with acute right lower quadrant pain, nausea, and anorexia. She was noted to have leukocytosis, anemia, and thrombocytopenia. Abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Other potential clinical presentation of leukostasis may include deep venous thrombosis , avascular bone necrosis , acute appendicitis , sudden cardiac death because of right‐sided cardiac mass , splenic rupture , acute kidney injury , retinopathy , and fever.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Other potential clinical presentation of leukostasis may include deep venous thrombosis , avascular bone necrosis , acute appendicitis , sudden cardiac death because of right‐sided cardiac mass , splenic rupture , acute kidney injury , retinopathy , and fever.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Other case reports also considered the nonsuppurative appendicitis as the initial manifestation of acute myelogenous leukemia [ 30 ]. A recent study linked acute appendicitis to acute myeloid leukemia [ 31 ]. Our study showed a strong relationship between appendicitis and haemopoietic malignancy, with an HR of 11.7 for the cancer to be diagnosed within 3 months after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Limited cases have been reported. [ 1 2 3 4 ] Most of the symptomatic cases happened in the course of leukemia relapse or progression. [ 2 3 ] Some were incidentally revealed by postmortem study.…”
mentioning
confidence: 99%
“…[ 1 2 3 4 ] Most of the symptomatic cases happened in the course of leukemia relapse or progression. [ 2 3 ] Some were incidentally revealed by postmortem study. [ 5 ] Although patients in the known setting of AML who develop abdominal pain after receiving chemotherapy are often found to have suppurative appendicitis after surgical intervention, acute leukemic appendicitis as the initial manifestation of AML proven on pathological review is even rarer,[ 3 4 ] and early recognition is difficult, especially when there is no obvious blasts in the peripheral blood like our case.…”
mentioning
confidence: 99%